Dzikir as a therapy in sufistic counseling - Sucipto, Ade (Journal of Advanced Guidance and Counseling, 2020)
This paper was aimed to provide knowledge that Dzikir can be used as an alternative therapy in sufistic counseling. Sufis have the view that all the problems faced by all individuals come from an uneasy heart or mind, so the first process of giving assistance to be done is to organize the heart or mind. Dzikir as a therapy in sufistic counseling is interesting to be studied further by using a grounded theory in qualitative research method. The results show that dhikr therapy is one of the sufistic counseling techniques that can be used to heal an uneasy heart or mind. Dzikir will make the counselee closer to the creator, namely Allah. In addition, dhikr makes the counselee aware of the essence of himself as a creature of God so that the powers of the soul emerge that will help the counselee overcome problems at hand.